Supplemental Material for 'Climate sensitivity of milk production traits and milk fatty acids in genotyped Holstein dairy cows' - Bohlouli, Mehdi; Justus Liebig University Giessen (My University, 2021)
The dataset includes supplementary figures S1-S3 and a table S1 for the manuscript accepted for publication in the Journal of Dairy Science.
JDS_Heat stress_supplemental Table S1 and and Figures S1-S3
Keywords: climate stress; reaction norm model; fatty acid profile; model stability; ddc:570; ddc:590